2015
DOI: 10.1016/j.jbiomech.2015.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell mechanics and calcium signalling in organotypic slices of human myometrium

Abstract: Elucidation of cellular mechanisms regulating myometrial contractility is crucial for improvement in management of many obstetric abnormalities, such as premature delivery, uterine dystocia and post-partum haemorrhage. Myometrial contractions are triggered by periodic synchronous rises in intracellular calcium concentration ([Ca2+]i) elicited by spontaneously generated action potentials propagating throughout the entire myometrium. During labour, hormones like oxytocin and prostaglandins potentiate uterine con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Oxytocin-induced [Ca 2+ ]i oscillations have been demonstrated in primary cultures of human uterine myocytes [ 98 , 99 ], but data recorded in intact cells residing within the myometrium are limited. However, a recent study on organotypic slices from human myometrium indicated that oxytocin-induced [Ca 2+ ]i oscillations occurred only in a proportion of cells and were not relevant for the acute regulation of myometrial contractility, but the authors suggested the involvement of [Ca 2+ ]i oscillations in long-term regulatory processes, e.g., gene expression triggering [ 100 ]. These cells were identified to be ICCs or ICLCs and described to be morphologically and phenotypically distinct by SMCs.…”
Section: Physiology and Alterations Of Calcium Signaling In Intersmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin-induced [Ca 2+ ]i oscillations have been demonstrated in primary cultures of human uterine myocytes [ 98 , 99 ], but data recorded in intact cells residing within the myometrium are limited. However, a recent study on organotypic slices from human myometrium indicated that oxytocin-induced [Ca 2+ ]i oscillations occurred only in a proportion of cells and were not relevant for the acute regulation of myometrial contractility, but the authors suggested the involvement of [Ca 2+ ]i oscillations in long-term regulatory processes, e.g., gene expression triggering [ 100 ]. These cells were identified to be ICCs or ICLCs and described to be morphologically and phenotypically distinct by SMCs.…”
Section: Physiology and Alterations Of Calcium Signaling In Intersmentioning
confidence: 99%
“…Modulation of TCs’ growth by mechanical factors via calcium channels has a degree of mechanical sensitivity [ 123 ] and correlates with the TCs’ ability to communicate through gap junctions [ 40 , 46 ], the calcium involvement in myometrium proliferation [ 154 , 155 ] and contraction [ 100 ]. Therefore, we propose the hypothesis that TCs contribute to smooth muscle growth in areas with high mechanical forces.…”
Section: Calcium Signaling In Tcsmentioning
confidence: 99%
“…Myometrial contraction is a prerequisite for natural parturition. It is mediated by elevated [Ca 2+ ] i [2][3][4]. Both SR Ca 2+ efflux [5,6] and extracellular Ca 2+ influx [7,8] in the myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the myometrium plays an essential role in regulating uterine quiescence and contraction, and progesterone and estrogen play important roles in regulating myometrium activities [1]. Similar as other muscle cell contractions, myometrial contractions are also mediated by elevated intracellular calcium concentration ([Ca 2+ ] i ), which is regulated by both Ca 2+ release from intracellular stores in the sarcoplasmic reticulum (SR) and Ca 2+ entry from the extracellular space [2][3][4]. Both SR Ca 2+ efflux [5,6] and extracellular Ca 2+ influx [7,8] in myometrial smooth muscle cells are important for myometrial contractions during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, compared to non-postpartum mice, lactating female mice show gene expression changes in the gonadotropes of the anterior pituitary gland in pathways relating to metal ion transport, cell adhesion, and positive regulation of cGMP metabolic processes (Qiao et al 2016). Finally, these physiological (Loftus et al 2015), immune system activation (Kimura et al 2006), and structural changes in the mammary gland, uterus, and ovaries (Thorne et al 2015). The ideas discussed above suggest a number of interrelated predictions.…”
Section: Conclusion and Future Research Avenuesmentioning
confidence: 99%